The haptic - audio navigation control to enhance interactivity of players in virtual reality game - Ahmad Hoirul Basori, author; Daut Daman, author; Mohd. Shahriza, author; Abdullah Bade, author; International Conference on Information & Communication Technology and Systems (4th : 2008 : Indonesia) (Skudai : Universiti Teknologi Malaysia, 2008)
PRZSL